Interactions among fruit fly pest larvae: Exploring competitive dynamics dmong Ceratitis capitata, Anastrepha fraterculus, and Drosophila suzukii in Argentina - Viana, Valeria Angelica; Bouvet, Juan Pedro; Pacelli, Franco; Milla, Fabian Horacio; Segura, Diego Fernando; Liendo, María Clara (Grupo de Trabajo en Moscas de la Fruta del Hemisferio Occidental (TWWH), 2024)
Presentación de diapositivas